Transition from spot to long-lived eruptive activity in continental rifting tracked by monitoring soil degassing - O. Munguiko Munyamahoro; G. Boudoire; E. Regis; S. Valade; D. Ciza; D. Coppola; R. Campion; P.-J. Gauthier; S. Maska; P. Mataba; G. Mavonga Tuluka; A. Tumaini Sadiki; et al. (Journal of Volcanology and Geothermal Research, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Shallow magma convection evidenced by excess degassing and thermal radiation during the dome-forming Sabancaya eruption (2012–2020) - D. Coppola; S. Valade; P. Masias; M. Laiolo; F. Massimetti; A. Campus; R. Aguilar; R. Anccasi; F. Apaza; B. Ccallata; C. Cigolini; L. F. Cruz; et al. (Bulletin of Volcanology, 2022)
We used a large set of satellite- (visible, infrared, and radar images from Planetscope, MODIS, VIIRS, Sentinel2, Landsat 8, and Sentinel 1) and ground-based data (optical images, SO 2 flux, shallow seismicity) to describe and characterize the activity of the Sabancaya volcano during the unrest and eruption phases that occurred between 2012 and 2020. The unrest phase (2012–2016) was characterized by increasing gas and thermal flux, sourced by a convective magma column rising along with the remnants of a buried plug still permeable to fluid flow. Conversely, a new conduit, adjacent to the previous one, fed the eruptive phase (2016–2020) which was instead characterized by a discontinuous extrusive activity, with phases of dome growth (at rates from 0.04 to 0.75 m 3 s −1 ) and collapse. The extrusive activity was accompanied by fluctuating thermal anomalies (0.5–25 MW), by irregular SO 2 degassing (700–7000 tons day −1 ), and by variable explosive activity (4–100 events d −1 ) producing repeated vulcanian ash plumes (500–5000 m above the crater). Magma budget calculation during the eruptive phase indicates a large excess of degassing, with the volume of degassed magma (0.25–1.28 km 3 ) much higher than the volume of erupted magma (< 0.01 km 3 ). Similarly, the thermal energy radiated by the eruption was much higher than that sourced by the dome itself, an unbalance that, by analogy with the degassing, we define as “excess thermal radiation”. Both of these unbalances are consistent with the presence of shallow magma convection that fed the extrusive and explosive activity of the Sabancaya dome.

MeMoVolc report on classification and dynamics of volcanic explosive eruptions - C. Bonadonna; R. Cioni; A. Costa; T. Druitt; J. Phillips; L. Pioli; D. Andronico; A. Harris; S. Scollo; O. Bachmann; G. Bagheri; S. Biass; et al. (Bulletin of Volcanology, 2016)

Mitochondrial and microsatellite DNA markers reveal a Balkan origin for the highly invasive horse‐chestnut leaf miner Cameraria ohridella (Lepidoptera, Gracillariidae) - R. VALADE; M. KENIS; A. HERNANDEZ‐LOPEZ; S. AUGUSTIN; N. MARI MENA; E. MAGNOUX; R. ROUGERIE; F. LAKATOS; A. ROQUES; C. LOPEZ‐VAAMONDE (Molecular Ecology, 2009)
Biological invasions usually start with a small number of founder individuals. These founders are likely to represent a small fraction of the total genetic diversity found in the source population. Our study set out to trace genetically the geographical origin of the horse‐chestnut leafminer, Cameraria ohridella , an invasive microlepidopteran whose area of origin is still unkown. Since its discovery in Macedonia 25 years ago, this insect has experienced an explosive westward range expansion, progressively colonizing all of Central and Western Europe. We used cytochrome oxidase I sequences (DNA barcode fragment) and a set of six polymorphic microsatellites to assess the genetic variability of C. ohridella populations, and to test the hypothesis that C. ohridella derives from the southern Balkans (Albania, Macedonia and Greece). Analysis of mtDNA of 486 individuals from 88 localities allowed us to identify 25 geographically structured haplotypes. In addition, 480 individuals from 16 populations from Europe and the southern Balkans were genotyped for 6 polymorphic microsatellite loci. High haplotype diversity and low measures of nucleotide diversities including a significantly negative Tajima’s D indicate that C. ohridella has experienced rapid population expansion during its dispersal across Europe. Both mtDNA and microsatellites show a reduction in genetic diversity of C. ohridella populations sampled from artificial habitats (e.g. planted trees in public parks, gardens, along roads in urban or sub‐urban areas) across Europe compared with C. ohridella sampled in natural stands of horse‐chestnuts in the southern Balkans. These findings suggest that European populations of C. ohridella may indeed derive from the southern Balkans.